Prosody training benefits in perception vs. production skills in simultaneous interpreting: an experimental study - Yenkimaleki, Mahmood (Dutch Journal of Applied Linguistics, 2021)
The present study investigates the prosody training benefits for interpreter trainees in perception vs. production skills in simultaneous interpreting. Two groups of student interpreters were formed. Participants were assigned to groups at random. The control group received routine instruction in interpreting skills. The experimental group spent 20 minutes less time per session on the routine curriculum and instead received awareness training on prosodic features of English. The total instruction time was the same for the students in two groups, i.e., 15 hours. Students then took a posttest in interpretation skills. The results showed that the experimental group performed better than the control group in simultaneous interpretation performance. Moreover, the study revealed that prosody training enhances the students’ perception skills more than that of the production skills. These results have pedagogical implications for curriculum designers, interpreter training programs, and all who are involved in language study and pedagogy.